Optimasi Seo (Search Engine Optimization) Dalam Meningkatkan Website Traffic Cimanggis Golf Estate - Lestiani, Novita; Priatna, Wahyu Budi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to describe the Search Engine Optimization (SEO) strategy implemented by Cimanggis Golf Estate to increase organic website traffic. The research employs a descriptive qualitative approach, using in-depth interviews with two key informants and participatory observation during an internship at the company. The findings reveal that the SEO strategy is applied comprehensively through three core areas: On Page SEO, Off Page SEO, and Technical SEO. Implementation includes developing relevant content, structuring headings properly, using meta tags and internal linking, and optimizing technical performance through page speed and mobile-friendly design. The company also builds digital reputation through article placements in reputable media and consistent content across the website and social media platforms. Challenges identified in the implementation include limited technical access due to third-party vendors and balancing visual appeal with SEO performance. Nevertheless, the CGE digital marketing team manages to address these issues through cross-functional collaboration and continuous evaluation. This research offers practical insight for property industry practitioners in leveraging SEO as part of a broader digital marketing strategy.